DELLA proteins: integrators of multiple plant growth regulatory inputs? - Alvey, L; Harberd, N (2005)
The DELLA proteins are a family of putative transcriptional regulators that inhibit the cell proliferation and expansion that drives the growth of plant organs. Plant growth is stimulated via destruction of DELLA proteins in the 26S proteasome. Recent advances have shown that the 'classical' phytohormones gibberellin (GA), auxin and ethylene control plant growth by influencing DELLA-destruction. This paper outlines the discovery, molecular characterization and biology of the DELLA proteins, and summarizes the evidence that they act as integrators of response to multiple growth-regulatory signals. Copyright © Physiologia Plantarum 2004.